Leaving rates and reasons for leaving in an Engineering faculty in South Africa: A case study - Jonathan Pocock (South African Journal of Science)
This paper describes a case study undertaken at the Faculty of Engineering of the University of KwaZulu-Natal to determine the leaving rates from the faculty both by a cohort analysis (over the existence of the university from 2005 to 2010) and by a 1-year population balance over the whole faculty in 2009. Students who had left the faculty who could have continued were identified from the population balance and interviewed to determine the common reasons for leaving. The cohort analysis showed that from 2005 through to 2008, the leaving rate from first-year cohorts was reduced year on year (from over 22% to below 14%). This reduction coincided with stabilisation of the faculty after a merger process and increased academic support. In 2009, however, an increase in the proportion of first-year students who left (to over 17%) was identified, which may be linked to the entry of students who had taken the new National Senior Certificate in South African high schools. The population balance over the year 2009 showed an academic exclusion rate of approximately 6% of the total undergraduate student body, and, more significantly, an academic leaving rate of about 14% of the total student body. The exclusion rate remained fairly static across three semesters whilst voluntary leavers increased over the same period. An analysis and interviews with a sample of the students who left showed that financial reasons played a significant role in these rates, with 49% of non-academically excluded students having financial difficulties, and that a significant proportion of students continue their studies at universities of technology. Although this is a case study within one institution, it is hoped that the findings can inform the current debate surrounding increasing throughput in Science and Engineering within the country.